2008
DOI: 10.1097/ajp.0b013e318171cdf1
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Correlates of Adjustment to Pain Among People With Multiple Sclerosis

Abstract: These findings provide support for the premise that psychosocial factors remain central in disability-related pain and suggest the possibility that interventions targeting these variables would reduce the negative impact of pain among people with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 61 publications
2
22
1
Order By: Relevance
“…In agreement with previous research (36), the relationships between education and both outcomes were found to act protectively, with more years of educations being associated with lower pain interference. Age was significantly associated with pain severity, with younger age associated with higher pain severity, which is consistent with previous pain studies (37,38).…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with previous research (36), the relationships between education and both outcomes were found to act protectively, with more years of educations being associated with lower pain interference. Age was significantly associated with pain severity, with younger age associated with higher pain severity, which is consistent with previous pain studies (37,38).…”
Section: Discussionsupporting
confidence: 81%
“…However, operant models of chronic pain suggest that pain contingent social support would result in increased disability, which may also provide a parsimonious explanation of the findings. The extent to which respondents with multiple sclerosis believed they were able to control or decrease their pain through use of their coping strategies has been found to be associated with decreased pain intensity, however no specific coping strategy was predictive (Douglas, et al, 2008). Further, in the same study no coping strategy was found to be predictive of life interference due to pain and only coping by increasing activities was found to be associated with improved psychological functioning.…”
Section: Behavioural Responses To Painmentioning
confidence: 51%
“…A belief that pain is constant or enduring has been found to significantly predict both pain intensity and interference to activities due to pain among those with multiple sclerosis (Douglas, et al, 2008). The lower endorsement of the belief that others should be solicitous in response to pain behaviours was associated with better psychological functioning among people with muscular dystrophy (Miro, et al, 2009) …”
Section: Cognitive Responses To Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Two good [9,53] and one medium quality study [10] examined the relationship between pain severity and pain catastrophizing. Two studies found medium to large positive bivariate relationships between pain severity and pain catastrophizing [9,10].…”
Section: Pain Catastrophizingmentioning
confidence: 99%